Case report: Treatment of intraductal papillary mucinous neoplasms located in middle-segment pancreas with end-to-end anastomosis reconstruction after laparoscopic central pancreatectomy surgery through a pigtail-tube-stent placement of the pancreatic duct - Liu, Guohua; Tan, Xiaoyu; Li, Jiaxing; Zhong, Guohui; Zhai, Jingwei; Li, Mingyi (Frontiers in Surgery, 2022)
Intraductal papillary mucinous neoplasms (IPMN) of the pancreas is one type of pancreatic cystic neoplasms (PCN). IPMNs can be classified into three types: main duct-IPMN(MD-IPMN), branch duct-IPMN(BD-IPMN), and mixed type-IPMN(MT-IPMN). It is universally accepted by most surgeons that patients who suffered from MD-IPMN with a high risk of malignant transformation should be carried out with surgical resection. However, the best surgical strategy for MD-IPMN located in the pancreatic neck still has not been a worldwide consensus. Recently, one patient suffering from this disease in our Minimally Invasive Pancreas Center has underwent a successful surgical procedure. In this case report, we performed a Laparoscopic central pancreatectomy(LCP) for this patient. During the surgical procedure, we used a method of end-to-end anastomosis’ reconstruction through the pigtail-tube-stent placement of the pancreatic duct. Before the construction of the remnant pancreas, surgical margins of the frozen section should be negative. After surgery, the outcome of this case was satisfactory. No complications such as postoperative hemorrhage（POH）, abdominal infection, pancreatitis, delayed gastric emptying(DGE) and clinically relevant postoperative pancreatic fistula(cr-POPF) occurred, which manifested this surgical strategy could achieve a good clinical therapeutic effect for the pancreatic neck MD-IPMN. The result of postoperative routine pathology confirmed the diagnosis of MD-IPMN. The pathological features also showed that there was a high degree of hyperplasia in the local epithelium, which indicated the necessity of surgical treatment.